Section 95(2) of the Street, Drainage and Building Act 1974: The Highland Towers’ Decisions - Abd Rahman, Faizah Nazri binti (Journal of Malaysian and Comparative Law, 2019)
The object of this paper is to study the application of s 95(2) of the Street, Drainage and Building Act 1974 ("SDBA") in the context of the current position of immunity afforded to local authorities against a duty of care in relation to building works in Malaysia. This will be done using the aforesaid case as case-study.